Register role and function in the arena of sociocultural practice (critical study of sociocultural practice) - Sujarwa Sujarwa; Andrik Purwasito; Sri Kusuma Habsari; Titis Srimuda Pitana (Universitas Ahmad Dahlan, 2023)
This paper is entitled